Characteristics of goal-scoring possessions in open play: Comparing the top, in-between and bottom teams from professional soccer league - Tenga, A.; Sigmundstad, E. (International Journal of Performance Analysis in Sport, 2011)
The purpose of this study was to compare how goals were scored from open play possessions between teams from the top three, in-between and bottom three positions of the final league-table in professional soccer. A sample of 997 goals scored from open play in the Norwegian top professional league during 2008, 2009 and 2010 seasons was analysed. Match performance analysis was performed on 10 variables based on four possession characteristics: type, number of passes, duration and starting zone. Results show that goals scored from counter attacks (P=0.001), possessions with 0-4 passes (P=0.005), possessions varied for 12 seconds or more (P=0.001 and P=0.012) and from possessions started in the midfield (P=0.002 and P=0.004) distinguished the bottom three teams. Only goals from possessions started in the midfield (P=0.013) managed to distinguish between the top three and in-between teams. The bottom three teams should consider more counter attacks with 0-4 passes and possessions of 12 seconds or more especially starting from the midfield zone in order to improve their goal scoring ability from open play possessions. And, in-between teams should consider more possessions starting from the midfield zone to raise their goal-scoring efficiency to the level of the top three teams.